Rancang Bangun Manajemen DSS Menggunakan Weighted Product - Muhyidin, Hafid; Nazwirman, Nazwirman (REMIK: Riset dan E-Jurnal Manajemen Informatika Komputer, 2019)
This study aims to build a decision support dashboard for new student selection candidates at Mts 4 Tangerang. To get students who are good criteria, the school holds a rigorous selection and sets the test threshold value. Selection of prospective new students is still manual, causing the selection process to be subjective. The method is used in the design of a Weighted Product system with a multi-criteria system. Functional modeling uses use case diagrams. This research produces a decision support application for the selection of new students. Assessment is carried out more objectively and relevant especially students who have good achievements in academic and non-academic fields. This application can accelerate the selection committee to do all the processes related to student acceptance.